2019
DOI: 10.1130/b35326.1
|View full text |Cite
|
Sign up to set email alerts
|

Two phases of post-onset collision adakitic magmatism in the southern Lhasa subterrane, Tibet, and their tectonic implications

Abstract: Abundant Neogene adakitic magmatism occurred in the southern Lhasa subterrane after the onset of the India–Asia collision while convergence continued. However, the tectonic setting and magmatic evolution of the adakitic rocks are still under discussion. This study includes new mineral chemical and whole-rock geochemical data as well as zircon U-Pb and Lu-Hf isotopes of adakitic intrusive rocks from the Gyaca and Nyemo locations in the southern Lhasa subterrane. Laser ablation–inductively coupled plasma–mass sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 107 publications
0
11
0
Order By: Relevance
“…(b) Longitudinal variations in post‐collisional adakitic and ultrapotassic rocks and rift initiation timing (Bian, Gong, Zuza, et al., 2020; Z. F. Guo et al., 2015; L. Y. Zhang et al., 2014, and references therein). Adakitic rocks can be divide into two groups, characterized by different fractionation evolutions of light and medium rare earth elements (Lu et al., 2020). The eastern cluster of adakitic rocks was triggered by the breakoff of Neo‐Tethyan oceanic slab, whereas others by lateral detachment of the Indian continental slab (Lin et al., 2021; Lu et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(b) Longitudinal variations in post‐collisional adakitic and ultrapotassic rocks and rift initiation timing (Bian, Gong, Zuza, et al., 2020; Z. F. Guo et al., 2015; L. Y. Zhang et al., 2014, and references therein). Adakitic rocks can be divide into two groups, characterized by different fractionation evolutions of light and medium rare earth elements (Lu et al., 2020). The eastern cluster of adakitic rocks was triggered by the breakoff of Neo‐Tethyan oceanic slab, whereas others by lateral detachment of the Indian continental slab (Lin et al., 2021; Lu et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Adakitic rocks can be divide into two groups, characterized by different fractionation evolutions of light and medium rare earth elements (Lu et al., 2020). The eastern cluster of adakitic rocks was triggered by the breakoff of Neo‐Tethyan oceanic slab, whereas others by lateral detachment of the Indian continental slab (Lin et al., 2021; Lu et al., 2020). The eastward‐younging trend of post‐collisional magmatism slowed down crossing the Yadong rift, which is consistent with the deceleration of the eastward propagation of rifting.…”
Section: Introductionmentioning
confidence: 99%
“…However, the Himalayan Orogen was a passive continental margin. Previous studies have shown that closure of the Neo-Tethys Ocean and initial of Indo-Asia collision occurred at 65-55 Ma [5][6][7], and breakoff of the subducted Neo-Tethys Ocean plate occurred at 37,39,40,47]. With comprehensive consideration of the regional geological setting, subducted-related adakitic rocks cannot be formed in the Himalayan Orogen during the Miocene, and geological signatures also disprove the hypothesis that the Kuday adakitic rocks originated from subducted ocean slab melting.…”
Section: Discussionmentioning
confidence: 93%
“…(1) delamination of thickened lithospheric root [26][27][28][29][41][42][43][44], (2) subducted Indian continental slab breakoff [19,20,[28][29][30][31][45][46][47] or rollback [38,48], and (3) slab-tearing of subducted Indian Plate [29,46,49,50].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, increasing studies have revealed that mantle‐derived mafic rocks are sometimes more isotopically enriched relative to the coexisting crustal felsic rocks, contrary to “standard” behavior (e.g., Jiang et al, 2018, and references therein; Shen et al, 2018). Furthermore, magmatic systems with such features commonly occur in regions associated with island arc accretion, such as the Central Asian Orogenic Belt (CAOB) (e.g., Huang et al, 2013; Shen et al, 2009, 2012) and Gangdese Belt (South Tibet) (e.g., Lu et al, 2019; Meng et al, 2019; R. Wang, Richards, Zhou, et al, 2015; Wang et al, 2016; Wang, Collins, et al, 2017; Wang, Weinberg, et al, 2018), but the relationship between the two processes (isotope inversion and island arc accretion) has not been clarified. Recently, Jiang et al (2018) have recognized an “reversed isotope” case in Gan‐Hang Belt (GHB) (South China), where the Neoproterozoic‐aged island arc rocks were locally exposed (Shu et al, 2019; Xia et al, 2018; Yao et al, 2019).…”
Section: Introductionmentioning
confidence: 99%